PENGARUH PEMBELAJARAN AKTIVITAS FISIK TERHADAP KEMAMPUAN LOMPATAN SMASH DALAM PERMAINAN BOLA VOLI SISWA KELAS VII SMP NEGERI 2 ELLA HILIR - Rahman Rahman; Nur Moh Kusuma Atmaja; Kurnia Dyah Anggorowati (STKIP Melawi, 2020)
ABSRAK.Effect of Physical Activity Learning Ability Against Leap Smash In Game Ball voliSeventh Grade Students of SMP N egeri 2 Ella Hilir . College of Teacher Training andEducation (STKIP) Melawi Study Program (Prodi) Health Physical Education andRecreation (PENJASKESREK), Supervisor 1. Nur Moh Kusuma Atmaja, M.Or, Supervisor 2,Kurnia Dyah Anggorowati, M.Or .The goal in this research was to determine the influenceof the learning activities of the physical on the ability to jump an smashes in a gameof football volleyball class VII SMP Negeri 2 Ella Hilir.The research used was quasiexperimental.The research design used in this study using